EARNED VALUE ANALYSIS TERHADAP BIAYA PADA PROYEK REHABILITASI JALAN GANDU – PANONGAN - Saepudin , Asep; Rijaluddin, Arief (Universitas Majalengka, 2019)
Good management is needed to control a construction project, in order to achieve the efficiency and effectiveness of project management, so that the results of the process of controlling costs, quality, and time are achieved that meet the planning. The method that can be used in controlling costs and time and can address the achievement of activities is the Method of Value Results Concept (EVC). Concept Method Value Results is a method of calculating the number of costs according to the budget in accordance with the work that has been completed or implemented. The Concept of Value Results Method can be used to analyze performance and make estimates of achievement of targets by using three indicators, namely ACWP (Actual Cost Work Performed), BCWP (Budgeted Cost of Work Performed), and BCWS (Budgeted Cost of Work Schedule). Rehabilitation of the Gandu Panongan road has CV values = 0 and CPI = 1 shows costs in accordance with the planned budget. And on the image of the variance analysis calculation integrated with the